Food insecurity in Piura, Peru, in the context of post-earthquake and the COVID-19 pandemic - Valladares-Garrido, Mario J.; Zapata-Castro, Luis E.; García-Vicente, Abigaíl; León-Figueroa, Darwin A.; Huamani-Colquichagua, Yanela; Huaman-Garcia, Mariana; Calle-Preciado, Raul E.; Valladares-Garrido, Danai; Díaz-Vélez, Cristian; Failoc-Rojas, Virgilio E.; Vera-Ponce, Víctor J.; Pereira-Victorio, César Johan (Frontiers in Public Health, 2023)
Seismic events can cause deficient nutritional intake and therefore changes in food security. The reduction in food intake is a long-term issue related to mental health disorders. Although Peru belongs to a seismic zone, there is little research on the impact on food security. In the context of the COVID-19 pandemic, we aimed to determine the factors associated with food insecurity after the 6.1-magnitude earthquake occurred in Piura, northern Peru, in 2021. A secondary analysis was performed in 177 people exposed to the earthquake in Piura. Food insecurity was assessed with the Household Food Insecurity Access Scale. Its association with insomnia, resilience, anxiety/depressive symptoms, and general variables were determined using generalized linear models. Food insecurity was observed in 31.1% (95% CI: 24.3-38.4) of participants. This prevalence was higher in people with mild (PR: 1.73, 95% CI: 1.12-2.70) and moderate (PR: 1.55, 95% CI: 1.09-2.22) anxiety symptoms, severe depressive symptoms (PR: 2.74, 95% CI: 1.24-6.03), and previous exposure to the El Niño Phenomenon (PR: 1.72; 95% CI: 1.06-2.81). An income higher than 5000 Peruvian soles (approximately 1300 US dollars) was associated with a lower prevalence of food insecurity (PR: 0.22, 95% CI: 0.13-0.40). Overall, three out of 10 individuals experienced food insecurity after the 2021 earthquake in Piura. Food insecurity may be aggravated by mental disorders, previous exposure to the El Niño phenomenon, and the COVID-19 pandemic. We suggest the development of preventive food security programs in the event of new seismic events.